KOMPOSISI LASAK BALENONG TAU AGAK - Evaldo Evaldo (Melayu Arts and Performance Journal, 2018)
ABSTRACT The composition of “Lasak Balenong Tau Agak” is inspired from the phenomenon of the travel drivers who experience many ups and downs in the roadway, whether with the passenger, other drivers, and other vehicles. This phenomenon is transformed into musical composition with various considerations correlated with its musical aspects. This composition is divided into three parts. First part is “Lasak” namely the phenomenon of travel drivers stigmatized as the reckless persons who have less controlled emotion that tends to end at the quarrel and accident. That phenomenon is embodied in the concept of musical disharmony. The second part is “Balenong” namely the travel route of the travel transport that starts from the departure point and returns to the initial point while utilizing the time as effective as possible. That travel route is analogized as a circle, embodied with the mathematical concept of music. The third part is “Tau Agak” namely travel drivers’ intelligence that can predict travel situation so, with their agility and compactness, they can drive fast and manage travel time well. This situation is analogized with the improvisation in playing the music. The methods used were first exploring the phenomenon of travel drivers and then capturing its essences into various atmospheres through several instruments namely erhu, lute, mandolin, accordion, dizzy, big talempong, small talempong, percussion set, and vocal. Keywords: Lasak Balenong Tau Agak, travel driver, disharmony, improvi-sation, talempong, gandang oguang.  ABSTRAK Karya komposisi musik “Lasak Balenong Tau Agak” terinspirasi dari fenomena supir travel yang banyak mengalami suka dan duka di jalan raya, baik dengan penumpang, sesama supir, dan kendaraan lainnya. Fenomena ini ditransformasi ke dalam garapan komposisi musik dengan berbagai pertimbangan yang dikorelasikan dengan aspek musikal Karya ini dibagi menjadi tiga bagian: Pertama, “Lasak”, fenomena supir travel dicap ugal-ugalan, emosi kurang terkontrol, bisa berujung pada pertengkaran dan kecelakaan. Fenomena tersebut diwujudkan dengan konsep disharmoni musik. Kedua, “Balenong”: rute perjalanan angkutan travel berawal dari titik keberangkatan dan kembali lagi ke titik awal, memanfaatkan waktu seefektif mungkin. Rute perjalanan itu dianalogikan seperti sebuah lingkaran, yang diwujudkan dengan konsep matematis musik. Ketiga, “Tau Agak”: kecerdasan para supir travel yang bisa memprediksi situasi perjalanan, sehingga dengan kegesitan dan kekompakan, mereka bisa melaju dengan cepat dan dapat mengelola waktu perjalanan dengan baik. Situasi ini dianalogikan dengan improvisasi dalam bermain musik. Metode yang digunakan  mengeksplorasi fenomena supir travel dan menangkap esensi-esensinya, kemudian ditransformasikannya ke berbagai suasana melalui beberapa instrumen erhu, kucapi, mandolin, akordeon, dizzy, talempong besar, talempong kecil, set perkusi dan vokal.